(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
Fake news spreads through digital platforms and thus has more and more intensity, affecting all aspects of social life. However, these companies are still not properly regulated. The objective of this work was to point out some initiatives that intend to regulate digital platforms in Brazil in order to combat disinformation. The methodology used for data collection was the bibliographical and documentary review, in an exploratory research with a qualitative approach. It is concluded that many bills have already been presented, however, these companies do not want to be regulated and are pressuring Congress to vote in their favor.